Civic Journalism as a Fortress of Democracy: An Analysis of the Dangers of Simulacra, Agitation, and Fake News - Rahma Lathifa Utami; Dinie Anggraeni Dewi; Agil Nanggala (CV. Ksatria Siliwangi, 2024)
The development of digital media has transformed patterns of public communication and journalistic practices, while simultaneously posing serious challenges to democracy, such as simulacra, media agitation, and the spread of fake news. These phenomena have the potential to create pseudo-realities, manipulate public opinion, and weaken public rationality and critical awareness. This study aims to analyze the role of civic journalism as a democratic safeguard in addressing the threats of simulacra, agitation, and hoaxes in the digital era. The research employs a descriptive method with a literature review approach, examining relevant books, journal articles, and previous research findings. The results indicate that civic journalism plays a crucial role in strengthening democracy by encouraging active citizen participation, presenting fact-based information, and expanding spaces for public discourse. However, the practice of civic journalism continues to face challenges, including low media literacy, limited information verification, and the dominance of social media algorithms. Therefore, strengthening digital literacy and journalistic ethics is essential.